2015
DOI: 10.1111/head.12649
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve and Vagus Nerve Stimulation, a Comprehensive Review: Part III

Abstract: Vagus nerve stimulation (VNS) is currently undergoing multiple trials to explore its potential for various clinical disorders. To date, VNS has been approved for the treatment of refractory epilepsy and depression. It exerts antiepileptic or antiepileptogenic effect possibly through neuromodulation of certain monoamine pathways. Beyond epilepsy, VNS is also under investigation for the treatment of inflammation, asthma, and pain. VNS influences the production of inflammatory cytokines to dampen the inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(84 citation statements)
references
References 91 publications
(183 reference statements)
3
81
0
Order By: Relevance
“…Another point that merits comments is the low frequency stimulation protocol used in this study for VNS that favors the activation of the efferent rather than afferent fibers of the VN [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Another point that merits comments is the low frequency stimulation protocol used in this study for VNS that favors the activation of the efferent rather than afferent fibers of the VN [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Treatment includes the use of devices that activate the auricular branch (termed Arnold's nerve) of the vagus nerve (8)(9)(10) and the cervical vagus nerve (found within the carotid sheath) (11). Cervical transcutaneous noninvasive vagus nerve stimulation (nVNS) has shown promising therapeutic effects in the treatment of acute and chronic migraine headaches (12)(13)(14), and acute and chronic cluster headaches (15), and is now FDA-approved to treat both episodic cluster (14) and acute migraine headaches (7,16,17). Recent work has shown that, with finite element modeling of cervical nVNS, the electrical field significantly penetrates the human neck and is sufficient to activate the cervical vagus nerve (11).…”
Section: Noninvasive Vagus Nerve Stimulationmentioning
confidence: 99%
“…It has many effects, which can by itself but more likely in concert with others exert the observed anti-seizure properties. These effects include desynchronization of neuronal activity, hippocampal plasticity, anti-inflammation and modulation of neurotransmitter release [10].…”
Section: Vns Mechanismmentioning
confidence: 99%
“…It induces anti-nociception by modulating multiple pain-associated structures in the brain and spinal cord affecting peripheral/central nociception, opioid response, inflammation process and pain-related behaviour [10]. VNS is currently undergoing many trials to explore its potential for various other clinical disorders: headache, arthritis, asthma, pain, fibromyalgia, bipolar disorder, and dementia [1].…”
Section: Vns Mechanismmentioning
confidence: 99%